PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH, IKLIM ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA GURU SMP NEGERI DI KECAMATAN PASAMAN KABUPATEN PASAMAN BARAT - Nofrina Nofrina; Bustari Muchtar (Program Studi Magister Manajemen, 2015)
This study aims to analyze (1) the principal effect of leadership style on organizational climate junior high school teacher in District Pasaman , (2) influence of the leadership style of the principal motivation of teachers working in the district Pasaman SMP N, (3) Effect of principal leadership style on performance of junior high school teacher in District Pasaman, (4) the effect of organizational climate on work motivation of teachers in District Pasaman SMP N, (5) organizational climate influence on the performance of junior high school teacher in District Pasaman N, (6) Effect of motivation on teacher performance SMP N in district Pasaman. Based on the results of the study can be seen that (1) the principal's leadership style significantly influence the organizational climate in Kecamaten Pasaman SMP N, (2) the principal's leadership style significantly influence the motivation of teachers working in the district Pasaman SMP N, (3) leadership style Principal significantly affect the performance of junior high school teacher in District Pasaman N, (4) organizational climate significantly influence the motivation of teachers working in the district Pasaman SMP N, (5) organizational climate had no significant effect on the performance of junior high school teachers in Kecamatn Pasaman N, (6 ) Motivation significant effect on the performance of junior high school teacher in District Pasaman. Keywords : leadership style, organizational climate, work motivation of teachers, and on performance